2016
DOI: 10.2174/1874325001610010797
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Arthroscopic Partial Meniscectomy in the Management of Degenerative Meniscus Tears: A Review of the Recent Literature

Abstract: Background:The use of arthroscopic partial meniscectomy for middle aged to older adults with knee pain is one of the most common surgical procedures with approximately 150,000 knee arthroscopies being carried out in the United Kingdom each year, and about five times that number in the United States. Despite this, the procedure remains controversial. The aim of this paper is to provide a comprehensive review of the role of arthroscopic meniscectomy in patients with degenerative meniscus tears and suggest recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
1
7
0
1
Order By: Relevance
“…Yim et al [45] performed a study comparing partial meniscectomies with nonoperative treatment methods and found no differences between the two groups in visual analog scale scores, Lysholm scores, Tegner activity scales, or subjective satisfaction. Other studies have shown similar results [5,39]. Taken together, the reported clinical lack of efficacy and the adverse biomechanical effects found in this study support avoiding partial meniscectomy in younger patients with minimal meniscal degradation to best maintain normal contact mechanics of the knee.…”
Section: Discussionsupporting
confidence: 77%
“…Yim et al [45] performed a study comparing partial meniscectomies with nonoperative treatment methods and found no differences between the two groups in visual analog scale scores, Lysholm scores, Tegner activity scales, or subjective satisfaction. Other studies have shown similar results [5,39]. Taken together, the reported clinical lack of efficacy and the adverse biomechanical effects found in this study support avoiding partial meniscectomy in younger patients with minimal meniscal degradation to best maintain normal contact mechanics of the knee.…”
Section: Discussionsupporting
confidence: 77%
“…5,52,54 Nevertheless, the role of arthroscopic surgery in the treatment of degenerative meniscal tears remains controversial. 2,30,33 A recent review concluded that these patients could benefit from arthroscopic meniscectomy but that nonsurgical treatment should be considered first. 29 Mechanical symptoms were previously considered an indication for surgery; however, recent data have contradicted this tenet.…”
mentioning
confidence: 99%
“…8,20,38 These high rates may reflect a need for more careful patient selection when considering meniscectomy. 2 After partial or total meniscectomy, the remaining treatment options are very limited for patients with persistent or recurrent pain. Current standards of care include nonsurgical interventions, such as intra-articular injections, unloading braces, and physical therapy.…”
mentioning
confidence: 99%
“… 8 , 20 , 38 These high rates may reflect a need for more careful patient selection when considering meniscectomy. 2 …”
mentioning
confidence: 99%